(untitled) (Al-Farooq Journal of Sciences, 2026)
What the researcher aims to achieve in this paper is not to delve into the historical roots and the moral and philosophical dimensions of tolerance; rather, we wish to address its moral and legal application in the present time, and attempt to overcome the dilemmas posed by this objective. Accordingly, our endeavor is directed towards monitoring and activating the concept of the philosophy of tolerance and recognition by presenting several ideas. This serves as a contribution to stimulating the dialogue we so desperately need at this time, which is marked by an escalation of fanaticism, violence, and intolerance. These phenomena have disrupted the foundations, principles, and values that govern the relationship with the "Other" to the point of excluding them intellectually, politically, and humanly. Indeed, the absence or marginalization of tolerance and recognition leads to the dominance of a mentality of prohibition and criminalization Thus, the tolerance hoped for today is not merely a moral or religious virtue, but rather an existential, social, cultural, and political necessity. This is crucial to safeguarding our daily lived reality against the dangers of fanaticism, extremism, violence, and intolerance that may surround us and target our existence and aspirations